Pengaruh Penggunaan Media Sosial terhadap Pemahaman Remaja Tentang Ajaran Agama Islam - Umami, Satria; Andayani, Dwi (Lembaga Yasin AlSys, 2023)
Understanding Islam is one of the important components that students must have in an effort to deepen or study so that in the future they do not misunderstand the values of Islamic teachings. There are various factors that can influence the level of Islamic understanding of each individual, both internal and external factors. Supporting students' achievement of a good Islamic understanding of information systems includes the ability to be critical, careful, wise, think objectively and appreciate the diversity of Islamic information obtained. This research aims to find out whether there is an influence of the use of social media on the Islamic understanding of Information Systems Students class of 2021. The research method used is a qualitative method with a case study approach. The data collection techniques used were questionnaires, interviews and documentation. The results of the research show that there is an influence of the use of social media on the Islamic understanding of Information Systems Students class of 2021 at Mataram University of Technology. The magnitude of the influence that social media has on Islamic understanding shows a figure of 21.2%. Social media has an influence in shaping students' mindsets, determining and developing understanding of the Islamic information they receive. Students who have good and strong personalities can determine their views and understanding of the information they receive, especially Islamic information. However, there are also some students who do not cross check the information they obtain.